"CHILD LABOR-FREE RAJASTHAN: AN AWARENESS STUDY" (International Journal of Food and Nutritional Sciences, 2023)
Child labor is a pervasive issue in Rajasthan, with thousands of children being forced to work in hazardous conditions, depriving them of their childhood and education. This study aims to investigate the effectiveness of awareness campaigns and community-based initiatives in reducing child labor in Rajasthan. The study employs a mixed-methods approach, combining both qualitative and quantitative data collection and analysis methods. The findings suggest that awareness campaigns and community-based initiatives can be effective in reducing child labor, but there are several challenges and limitations that need to be addressed. The study recommends a comprehensive framework for combating child labor in Rajasthan, involving the government, NGOs, and local communities.